EGFL7 and RASSF1 promoter hypermethylation in epithelial ovarian cancer - Yanisa Rattanapan (2019)
© 2018 Elsevier Inc. DNA methylation is one of the epigenetic mechanisms associated with gene expression and plays a key role as in activation and deactivation of oncogenes and tumor suppressor genes, respectively. This study employed DNA methylation array to identify methylated genes which are highly correlated with various phenotypes of epithelial ovarian cancer (EOC) in Thai patients and to quantify promoter CpG-island methylation of candidate genes. Tissues from patients with serous and non-serous EOC showed significantly higher promoter methylation of EGFL7 and RASSF1 compared to benign cases. These results indicate the potential of investigating promoter CpG-island methylation of cancer-associated genes as biomarkers of disease progression and even possibly of early detection.